Beyond glitter and glue: The significance of context in including children with intellectual disability in well-being research - Lise Mogensen; Jenny McDonald; Jan Mason (Social Work and Society)
It is common for children with disability to be excluded from research and from participation in contributing to policy and practice strategies for their well-being. The research reported in this paper attempted, through piloting inclusive methods, to respond to moral, practical and conceptual imperatives of enabling children with disability to participate in research. The article describes the researchers' use of child-inclusive, qualitative methodology, to understand how children with intellectual disability and/or 'communication difficulties' define and experience child well-being. We demonstrate the importance of flexibility and reflexivity in choosing and using methods to engage children. The findings reported highlight the ethical dilemmas in research with children and indicate the significance context has for the design of data collection strategies and analysis of data. Conclusions emphasise the importance and possibility of challenging barriers to the inclusion of children with intellectual disability as participants in research, with lessons for research more generally.